ALLERGIC RHINITIS IN PRE-SCHOOL CHILDREN LIVING IN URBAN SETTINGS OF THE ALTAI REGION: A POPULATION-BASED CROSS-SECTIONAL STUDY - Natalia V. Shakhova; Elena M. Kamaltynova; Yuriy Ph. Lobanov; Tatyana S. Ardatova ("Paediatrician" Publishers LLC, 2018)
Background. It is necessary to study the prevalence and risk factors of allergic rhinitis (AR) among pre-school children in order to develop a disease prevention strategy.Objective. Our aim was to study the prevalence, clinical and allergological features, and risk factors for AR in pre-school children living in urban settings of the Altai Region.Methods. At the screening stage, the study enrolled children aged 3-6 years attending pre-school educational institutions in 5 cities of the Altai Region. AR symptoms were determined using the ISAAC questionnaire. The AR was diagnosed if ≥ 2 symptoms (rhinorrhea, nasal breathing difficulty, itching in the nasal cavity, repetitive sneezing) lasted ≥ 1 h with a positive prick test and/or a blood level of specific IgE > 0.35 kU/L to at least one allergen (total 11).Results. The prevalence of AR in urban children aged 3-6 years (n = 3,205) was 10.6%; 48% of them were previously diagnosed with AR. 85% of children had a persistent course of the disease; 69% had mild AR. Most often, there was established sensitization to house dust mites (61.6%), birch pollen (40.9%), and cat fur (19.4%). The risk factors for AR were family history of allergies [odds ratio (OR) 4.2; 95% confidence interval (CI) 3.5-5.9], masculine (OR 2.8, 95% CI 1.9-4.0), smoking parents (OR 1.8, 95% CI 1.2-2.9), nonadherence to a regimen/dosage of vitamin D3 intake in infancy (OR 1.8, 95% CI 1.2-2.8), presence of asthma-like symptoms (OR 10.2, 95% CI 7.2-14.5), and manifestations of atopic dermatitis (OR 6.0, 95% CI 4.2-8.5).Conclusion. AR occurs in every tenth pre-school child (mainly of mild severity and persistent course), every second disease among them was diagnosed for the first time. Sensitization occurs to typical for childhood allergens. The risk factors for AR are family history of allergies, masculine, passive smoking, ignoring the recommendations of taking vitamin D3 in infancy, the presence of atopic dermatitis, and asthma-like symptoms.